Coherent photoproduction of heavy quarkonia on nuclei - Kopeliovich, Boris Z.; Krelina, Michal; Nemchik, J.; Potashnikova, I. K. (Physical review, 2022)
The differential cross section of coherent photoproduction of heavy quarkonia on nuclear targets is calculated within the QCD color dipole formalism. The higher-twist nuclear shadowing corresponding to the ¯QQ Fock component of the photon is calculated including the correlation between dipole orientation →r and impact parameter of a collision →b, which is related to the transverse momentum transfer via the Fourier transform. We also included the leading-twist gluon shadowing corresponding to higher Fock components of the photon containing gluons, which have specifically short coherence time, especially for multigluon components, even at very high energies. The contribution of such fluctuating gluonic dipole is calculated employing the path-integral technique. Our results are in good agreement with recent ALICE data on charmonium production in ultraperipheral nuclear collisions.